Operative management of chondrosarcoma in pelvic region: case series - Wiratnaya, I Gede Eka; Wirabhawa, Made; Sandiwidayat, Komang Septian; ., Aakash (International Journal of Research in Medical Sciences, 2019)
Chondrosarcoma is the second most frequent malignant bone tumour after osteosarcoma. It most often occurs in the pelvis. Treatment of pelvic chondrosarcoma is a difficult problem for the musculoskeletal oncologist. We report 3 patient with chondrosarcoma in pelvic region that undergoing internal hemipelvectomy. First patient, male 28 y.o. with chondrosarcoma in left iliac wing 11.2cm x 10.8cm x 9.2cm. Second, woman, 47 y.o with chondrosarcoma in right superior and inferior pubic rami 13.7cm x 11.5cm x 14.2cm with soft tissue mass around extended to medial part of proximal thigh. Already done A wide excision of the tumor was performed and we use non-vascularized fibular graft (NVFG) to fill the defect. Last patient, pregnant woman 22 y.o. (16weeks gestational age) with chondrosarcoma in right pubic rami 9.8cm x 11.4cm x 13cm. We already done internal hemipelvectomy without terminating the fetus. The second and third patient confirmed with the histopathology result with chondrosarcoma grade II, and the first patient with chondrosarcoma grade I. After 3month post operatively, all of the patients have no pain, no urinary tract complain. The first patient can ambulatory full weight bearing with no crutches or walker. Second patient ambulatory partial weight bearing with crutches. The last patient ambulatory with wheel chair during the pregnancy. Since chondrosarcomas are unresponsive to chemotherapy or radiotherapy, surgical resection was the only therapeutic solution for these patients. It also reinforce the need of a correct diagnose and collaboration between specialities in the treatment of oncological patients.